Draft Annual Plan 1978-79 (In 4 Volumes) Vol. II Haryana State - Planning Commission (Planning Commission, 1978)
Before enunciating the strategy for the annual plan 1978-79, it is imperative to highlight the achievements made during last three years and anticipated achievements of the fourth year of the Fifth Plan. In 1974-75, the first year of though Fifth Plan, agro-climatic conditions remained quite unfavourable which affected the agricultural production considerably.
Planning Department, Government of Haryana